-30/5x-25 added to 4x-5/x-5?

rational expression

2 Answers
Nov 18, 2017

(4x-11)/(x-5)

Explanation:

Make both denominators equal, then you can add the top lines.

-30/(5x-25)+(4x-5)/(x-5)

Divide the LHS equation by 5, top and bottom:
=-6/(x-5)

So now you have -6/(x-5)+(4x-5)/(x-5)

Combining them gives (-6+4x-5)/(x-5)
=(4x-11)/(x-5)

Nov 18, 2017

=> (4x-11)/(x-5)

Explanation:

-30/(5x-25)+( 4x-5)/(x-5)?

=>-30/(5(x-5)) + (4x-5)/((x-5))

=>-cancel30^6/(cancel5^1(x-5)) + (4x-5)/((x-5))

=>-6/(x-5) +(4x-5)/(x-5)

=> (-6+4x-5)/(x-5)

=> (4x-11)/(x-5)